Integrated seawater intrusion study of coastal region of Thiruvallur district, Tamil Nadu, South India - S. Senthilkumar; K. Vinodh; G. Johnson Babu; B. Gowtham; V. Arulprakasam (Applied Water Science, 2019)
Abstract The groundwater is the main resource of water for irrigation activity in river lacking area. The freshwater–seawater interface in the study region that has existed 3 km away from the coast in the year 1969 has been found to be migrated to distance of 13 km from the coast during the year 2007 noticed by the Central Ground Water Board (Central ground water board’s district groundwater brochure, Thiruvallur district, Tamil Nadu, 2007). Integrated geochemical and geophysical techniques were carried out in the study area to decode subsurface geologic pattern and delineate the seawater–freshwater zones. Total numbers of 50 samples were collected from the entire study area and analyzed for major ions. The considerable samples are brackish scenery of groundwater water at low depth. Chadha and Piper’s plots categorize the coastal groundwater into Na–HCO3, Ca–Na–HCO3, Ca–HCO3, and Na–Cl water facies, with Ca–HCO3 as the dominant. Cl/CO3 + HCO3 ratio, Cl/HCO3, and ionic strength, Mg/Ca and Cl/HCO3 ratios show that most of the samples in the study area are affected by seawater intrusion, which is also confirmed by the geophysical method. The results of vertical electrical sounding carried out in the study area reveal the low transverse resistance and high longitudinal conductance. It suggests the brackish nature of the groundwater in the eastern part of the study area may be due to the seawater intrusion. The final map using GIS platforms productively delineates the location that is really undergoing seawater and freshwater zone is migrated toward the inland. The article suggested further studies to arrest the migration of sea/freshwater interface into the land and avoid overexploitation of groundwater to further development.